Pengaruh Tingkat Kompetisi Domestik terhadap Performa Ekspor Perusahaan Manufaktur Indonesia (Jurnal Kebijakan Ekonomi, 2019)
Domestic competition has an influence on the export performance of the firm. Based on theory, the influence will vary depending on the level of efficiency owned by the firm. Using the data of large industrial companies currently manufacturing from 2002 to 2014 aggregated into the ISIC rev 3 3-digit sector, this study shows that domestic competition will have a positive influence on export performance in sectors with low and medium technology levels. While in high technology sectors, domestic competition has a negative effect on export performance.